1996
DOI: 10.3109/10428199609054810
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Implications of Bone Lesions in Childhood Leukemia at Diagnosis

Abstract: We studied 168 children with acute lymphoblastic leukemia (ALL) and 57 with acute nonlymphoblastic leukemia (ANLL) by retrospectively analyzing clinical symptoms, bone or joint involvement, and hematological findings to verify the clinical features and prognosis of children with acute leukemia who showed radiographic bone changes at the time of diagnosis. Of these, 36 with ALL (21.4%) and 6 with ANLL (10.5%) had symptoms referable to the bones or joints. Thirteen patients (7.7%) with ALL showed bone lesions ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…There have been only a small number of case reports in which various hypercalcemia‐associated factors were examined, and the prognoses have also been described in few reports (Table 2). In the past, some researchers have suggested that bone lesions at the initial presentation of childhood ALL are associated with good prognosis 33,34, and another retrospective report suggested that bone involvement had no association with the prognosis 35. In the above‐mentioned study on four cases of hypercalcemia from a single institute, no association was found between hypercalcemia and prognosis 30.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a small number of case reports in which various hypercalcemia‐associated factors were examined, and the prognoses have also been described in few reports (Table 2). In the past, some researchers have suggested that bone lesions at the initial presentation of childhood ALL are associated with good prognosis 33,34, and another retrospective report suggested that bone involvement had no association with the prognosis 35. In the above‐mentioned study on four cases of hypercalcemia from a single institute, no association was found between hypercalcemia and prognosis 30.…”
Section: Discussionmentioning
confidence: 99%
“…6 There are conflicting reports as to whether skeletal involvement at diagnosis has an influence on prognosis. [7][8][9] Bone metabolism at diagnosis…”
Section: Skeletal Morbidity At Diagnosis Of Childhood Allmentioning
confidence: 99%
“…6 There are conflicting reports as to whether skeletal involvement at diagnosis has an influence on prognosis. [7][8][9] Bone metabolism at diagnosis At diagnosis, serum markers of bone formation, procollagen type I C-terminal propeptide (PICP) and bone alkaline phosphatase (AP), are significantly lower than expected. 10,11 Low concentrations of the bone collagen degradation peptide, carboxyterminal telopeptide of type I collagen (ICTP), have also been demonstrated.…”
Section: Skeletal Morbidity At Diagnosis Of Childhood Allmentioning
confidence: 99%
“…Bone or joint pain can be one of the presenting symptoms in leukemic children. Patients may be incorrectly diagnosed and treated for osteomyelitis or juvenile inflammatory arthritis several months prior to ALL diagnosis [2]. Additionally, osteomyelitis itself is a known presenting symptom and complication of ALL [3].…”
Section: Discussionmentioning
confidence: 99%
“…persistently throughout both workup and treatment. It has been reported that nearly normal hematologic values are associated with certain cases of ALL involving bone pain [2,7,8]. One retrospective review of 296 patients [8] found that those presenting with the primary complaint of bone pain, compared with those with predominant symptoms of another type, tended towards nearly normal hemoglobin concentration, leukocyte, absolute neutrophil, and platelet counts.…”
Section: Case Presentationmentioning
confidence: 99%